Arrhythmic Burden in Cardiac Amyloidosis: What We Know and What We Do Not - Alessia Argirò; Annamaria Del Franco; Carlotta Mazzoni; Marco Allinovi; Alessia Tomberli; Roberto Tarquini; Carlo Di Mario; Federico Perfetto; Francesco Cappelli; Mattia Zampieri (Biomedicines, 2022)
Cardiac amyloidosis (CA), caused by the deposition of insoluble amyloid fibrils, impairs different cardiac structures, altering not only left ventricle (LV) systo-diastolic function but also atrial function and the conduction system. The consequences of the involvement of the cardiac electrical system deserve more attention, as well as the study of the underlying molecular mechanisms. This is an issue of considerable interest, given the conflicting data on the effectiveness of conventional antiarrhythmic strategies. Therefore, this review aims at summarizing the arrhythmic burden related to CA and the available evidence on antiarrhythmic treatment in this population.